2000
DOI: 10.1034/j.1600-0404.2000.102006378.x
|View full text |Cite
|
Sign up to set email alerts
|

Unawareness of deficits after right hemisphere stroke: double-dissociationsof anosognosias

Abstract: Double-dissociations demonstrate that anosognosias for different defects are independent and specific impairments of awareness, although general cognitive disorder may also reduce awareness of defects. Unawareness of illness and anosognosia for hemiparesis disappear rapidly and can hardly be direct causes of poor long-term recovery. However, transient anosognosia may be associated with persistent disorders which result in poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
3
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 11 publications
5
40
3
4
Order By: Relevance
“…First, the study brings forth other data on the functional recovery of patients with N. Second, the study shows that patients with A have more severe cognitive disturbances than those of subjects with N. This is in line with data by Feinberg et al, 3 Stone et al, 23 and Jehkonen et al, 24 which underline that A is an indicator of more severe neglect. Finally, it increases the knowledge on the factors affecting the rehabilitative outcome of subjects with N. There are few studies on this topic.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…First, the study brings forth other data on the functional recovery of patients with N. Second, the study shows that patients with A have more severe cognitive disturbances than those of subjects with N. This is in line with data by Feinberg et al, 3 Stone et al, 23 and Jehkonen et al, 24 which underline that A is an indicator of more severe neglect. Finally, it increases the knowledge on the factors affecting the rehabilitative outcome of subjects with N. There are few studies on this topic.…”
Section: Discussionsupporting
confidence: 78%
“…First, the cognitive disturbances found in subjects with NϩA pertain to A itself. 3,24,25 In fact, Jehkonen et al 24 found that patients with A had poorer orientation and verbal memory, and Feinberg et al 3 observed verbal confabulation in subjects with A. Starkstein et al 25 found significantly higher frequencies of hemispatial neglect and related phenomena, as well as deficits in recognizing facial emotions and in receptive prosody in patients with A. Second, in our study we wanted to take more into consideration the motor FIM score, which assesses self-sufficiency in the activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the clinical diagnosis, in patients with neglect we administered four tests: line crossing, letter cancellation, figure and shape copying, and line bisection (Jehkonen et al, 2000). All patients with neglect scored pathologically in at least 2 of these tests.…”
Section: Unawareness Evaluationmentioning
confidence: 99%
“…Only patients within the first 3 months from the acute stroke were included because it is well established that unawareness phenomena are not stable and may have a progressive recovery within the first months, so that it is much more evident in the acute phase than in the following period (Jehkonen et al, 2000;Marcel et al, 2004). The diagnosis of stroke was based on the clinical history and magnetic resonance (MR) findings.…”
Section: Subjects and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation